Development of supply and demand models of rice in lower Mekong river basin countris : (JIRCAS, 2010)
Contents: Development of the Rice Econometric Model with Endogenous Water in Lao PDR, Cambodia, Thailand and Vietnam, Development of the Rice Econometric Model with Endogenous Water in Lower Mekong Countries,...